Direct parallel electrosynthesis of high-value chemicals from atmospheric components on symmetry-breaking indium sites - Sun, Yuntong (2025)
To tackle significant environmental and energy challenges from increased greenhouse gas emissions in the atmosphere, we propose a method that synergistically combines cost-efficient integrated systems with parallel catalysis to produce high-value chemicals from CO2, NO, and other gases. We employed asymmetrically stretched InO5S with symmetry-breaking indium sites as a highly efficient trifunctional catalysts for NO reduction, CO2 reduction, and O2 reduction. Mechanistic studies reveal that the symmetry-breaking at indium sites substantially improves d-band center interactions and adsorption of intermediates, thereby enhancing trifunctional catalytic activity. Employed in a flow electrolysis system, the catalyst achieves continuous and flexible production of NH3, HCOO-, and H2O2, maintaining over 90% Faradaic efficiency at industrial scales. Notably, the parallel electrolysis device reported in this study effectively produces high-value products like NH4COOH directly from greenhouse gases in pure water, offering an economically efficient solution for small molecule synthesis and unique insights for the sustainable conversion of inexhaustible gases into valuable products. Therefore, this work possesses considerable potential for future practical applications in sustainable industrial processes.